Recent Progress of the Practical Applications of the Platinum Nanoparticle-Based Electrochemistry Biosensors - Yu, Han; Yu, Jingbo; Li, Linlin; Zhang, Yujia; Xin, Shuquan; Ni, Xiuzhen; Sun, Yuan; Song, Kai (Frontiers in Chemistry, 2021)
The detection of biomolecules using various biosensors with excellent sensitivity, selectivity, stability and reproducibility are of great significance in the analytical and biomedical fields towards achieving their practical applications. Noble metal nanoparticles are favorable candidates due to their unique optical, surface electrical effect and catalytic properties. Amongst, platinum nanoparticles (Pt NPs) have been widely employed for the detection of the bioactive substances, such as glucose, glutamic acid and hormones. However, there is a still long way to go before fully overcoming the potential challenges in their practical applications. Bearing this in mind, combined with our research experience, we summarized the recent progress of the Pt NPs-based biosensors and highlighted the current problems existed in the practical applications. The current review would provide fundamental guidance for future applications using the Pt NPs-based biosensors in food, agricultural and medical fields.